Section 8 orders on the public-private law divide*. Issue 1 (2nd January 2017) - Harding, Maebh; Newnham, Annika
Abstract: While section 9(2) of the Children Act 1989 prevents a Local Authority from applying for a child arrangements order directly, a case file study of residence and contact orders made in 2011 found that a significant number of applications for residence orders in the County Court were supported and sometimes even instigated by local authority children's services (Harding & Newnham, 2015). The findings of the study demonstrate that residence orders often formed part of solutions offered to the family and can even operate as an alternative to formal public law remedies in situations where the parents are no longer able to provide care, and grandparents or other relatives take over. In these 'hybrid cases' private law orders are used to resolve situations on the fringes of public law action and, in some cases, divert cases from voluntary accommodation or formal care proceedings. This article raises questions about whether cases are being diverted to private law remedies in an appropriate manner and argues that closer scrutiny of the practice is required to ensure that the rights of parents, children and kinship carers are appropriately respected.